3p+1=13

Simple and best practice solution for 3p+1=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3p+1=13 equation:


Simplifying
3p + 1 = 13

Reorder the terms:
1 + 3p = 13

Solving
1 + 3p = 13

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 3p = 13 + -1

Combine like terms: 1 + -1 = 0
0 + 3p = 13 + -1
3p = 13 + -1

Combine like terms: 13 + -1 = 12
3p = 12

Divide each side by '3'.
p = 4

Simplifying
p = 4

See similar equations:

| 8(3a-52)-4(2a+3)=12 | | -9n-10=-100 | | 12x+11=14x+1 | | 17t+15=11t+51 | | 6y-15=-5y+18 | | (4n-1)(2n+4)= | | 4y+4=3y-6 | | 8x+3=13+3x | | (5a^2x+3ax^2-5x)+(2a^2x-5ax^2+7x)= | | 12x-10=62 | | -5(X+3)2(x-1)=-14 | | 8(2)+5= | | -9w-19=4w-6 | | -9-(4)(2)(x)=3249 | | 8x^2-21x+10=0 | | 8x^2-1x-9=0 | | 10w+16=10w+16 | | 3.2q-4.1-4.6q=-2.4q-3.2 | | 1+p+5+p=-2 | | 6r(2r-1)= | | 5x+24=12x+60 | | 6m+10=25-m | | 5x+11=12x+60 | | (5x^2-x-7)+(2x^2+3x+4)= | | 20e+50f=8(40) | | 22x-26x=10-14 | | -10-8x=-110+6 | | 3x-5y-4y+9x+2= | | 2xa-11=-5 | | 5x=48+2x | | (5x+3o)+9o= | | -3(4)+-2=x |

Equations solver categories